The role of xylulose as an intermediate in xylose conversion to furfural: insights via experiments and kinetic modelling. Issue 82 (5th September 2015) - Ershova, O.; Kanervo, J.; Hellsten, S.; Sixta, H.
<x xml:space="preserve">Abstract</x> An experimental work has been performed to study the relevance of xylulose as an intermediate during non-catalyzed and acid-catalyzed xylose conversions to furfural in aqueous solution at the temperature range from 180 to 220 °C.